And we rise : the Civil Rights Movement in poems - Martin, Erica (Halcyenda Erica) (Viking, 2022)
Contains a collection of poetry by Erica Martin about both well-documented and lesser-known people and events of the Civil Rights Movement. Includes black-and-white photographs, a timeline, and additional resources.